Rubberwood- A problem for moulders ? - Gloeckner R (In: Proceedings of the International Rubberwood Seminar, 21-22 May 1990, Kuala Lumpur, Malaysia, pp.21-26., 1990)
The paper deals with the suggestions for making end products such as furniture, moldings etc from rubber wood by overcoming the limitations. The suggestions include a series of procedure, to be adopted, starting from the kiln drying of rubber wood to the manufacture of finished products. The article also provides suggestions for adopting suitable machineries and tools.
Keywords: Moulding; Rubberwood